A review of cytokine-based pathophysiology of Long COVID symptoms - Low, Russell N.; Low, Ryan J.; Akrami, Athena (Frontiers in Medicine, 2023)
The Long COVID/Post Acute Sequelae of COVID-19 (PASC) group includes patients with initial mild-to-moderate symptoms during the acute phase of the illness, in whom recovery is prolonged, or new symptoms are developed over months. Here, we propose a description of the pathophysiology of the Long COVID presentation based on inflammatory cytokine cascades and the p38 MAP kinase signaling pathways that regulate cytokine production. In this model, the SARS-CoV-2 viral infection is hypothesized to trigger a dysregulated peripheral immune system activation with subsequent cytokine release. Chronic low-grade inflammation leads to dysregulated brain microglia with an exaggerated release of central cytokines, producing neuroinflammation. Immunothrombosis secondary to chronic inflammation with microclot formation can lead to decreased tissue perfusion and ischemia. Intermittent fatigue, Post Exertional Malaise (PEM), CNS symptoms with "brain fog", arthralgias, paresthesias, dysautonomia, and GI and ophthalmic problems can consequently arise as result of the elevated peripheral and central cytokines. There are abundant similarities between symptoms in Long COVID and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). DNA polymorphisms and viral-induced epigenetic changes to cytokine gene expression may lead to chronic inflammation in Long COVID patients, predisposing some to develop autoimmunity, which may be the gateway to ME/CFS. There are abundant similarities between symptoms in Long COVID and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). DNA polymorphisms and viral-induced epigenetic changes to cytokine gene expression may lead to chronic inflammation in Long COVID patients, predisposing some to develop autoimmunity, which may be the gateway to ME/CFS.